Uses of conventional and novel expertise development to study microleakage in tooth restoration using composite resin - Masudi, Sam'an Malik; Sulaiman, Nik Roslin Suraini Nik (2002)
The present invitro study was conducted to evaluate microleakage at the enamel and dentin cavity walls of Class V composite restorations using 'multistep adhesive technique' and compared with 'single-step adhesive technique'.Twenty freshly extracted human premolar teeth were used and V-shaped cavity design with margins in enamel and dentin are prepared on the buccal surfaces of the premolar teeth, using diamond burs after which they were further divided randomly into two groups. Dimension of the preparation are 4 mm in length, 3 mm in width and 2 mm in depth. The prepared cavities were then restored with Alpha-dent Visible light-cure hybrid-type composites (Dental Technologies, Inc.). For Multi-Step technique, the etchant is Alphadent Etching liquid 35°/o phosphoric acid by weight and Bonding agent (combined with Primer) used in this study is Alpha-dent light cure Enamel/Dentin bonding resin. For Single-Step technique, the etching-bonding liquid used in this study is AQ Bond (SUN Medical Co. Ltd.). After finishing and polishing, teeth were thermo-cycled 800 times; 5-55° C and 20 s. dwell time. The teeth were sectioned longitudinally using double-sided diamond disc with mandrel placed on Amman AF350 cutting machine, to form a dimension of 2 mm thick and 10 mm in diameter.Specimens were then ground and polished on one side with fine grits of silicone carbide paper using Knuth Rotor water cooled polishing machine under 10,000 rpm. The prepared specimens were fixed to SEM stub using double-sided adhesive tape and observed on the Scanning Electron Microscope (SEM).The ultra structure was investigated directly using the Scanning Electron Microscope (SEM) without die penetration. Photomicrographs were taken of representative areas (from 0 to 3 in the cavity walls) where area (1) is on enamel of the occlusal wall; area (2) is on dentin and area (3) is on enamel of cervical wall of the cavity at magnifications of 1.000 times for further quantitative marginal analysis. Five photomicrographs were taken for each specimen. Statistical analysis by STATA and Student t-test was performed and correction for comparisons at p< or = 0.05. It was concluded in this study that Single-Step technique showed no different result in reducing microleakage compared to Multi-Step technique and therefore can be used as an alternative treatment in the clinic. Single-Step technique showed significantly lower leakage compared to Multi-Step technique in dentin, but showed no statistically significant differences in occlusal and cervical enamel.